Application Of Wastewater Treatment Technology In Tofu Industry, Pekanbaru City - Elvi Yenie; Eriyati; Ida Zahrina (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Tofu industry produce wastewater with low pH and high pollutant parameters, such as BOD, COD, TSS. Therefore, it is necessary to have a wastewater treatment plant so as not to pollute the environment and cause health problems. The purpose of this community service activity is the application of appropriate technology for processing liquid waste in the tofu industry in Pekanbaru City with a combination of equalization, filtration and phytoremediation processes. This service activity includes several stages, namely counseling to provide understanding to partners about the importance of treating waste, followed by building a liquid waste treatment plant and the application of liquid waste treatment technology. The sewage treatment plant consists of 3 concrete tanks that consisting of equalization, filtration (using coral, porous plastic, jute, gravel, and sand as filter media) and phytoremediation (using water hyacinth plants). This activity has a very positive effect for the owners of tofu industry. The levels of BOD, COD and TSS decreased significantly after the application of this wastewater treatment technology.